Association between low serum folic acid and vitamin B12 levels with COVID-19 prognosis - Keskin , Olgun; Seremet Keskin , Ayşegül; Nilgün Seremet (Progress in Nutrition, 2022)
Background and aim: It is important that the immune system is active and strong in protection from the COVID-19 pandemic. Folic acid and vitamin B12 involved in the initiation, maintenance and regulation of both innate and adaptive immune reactions of the host against the infections. In this study, it was aimed to investigate the relationship between serum folic acid and vitamin B12 levels of COVID-19 patients on the prognosis of the disease. Methods: The sample of the study consists of 529 individuals hospitalized in the Pandemic Chest Diseases Intensive Care Unit. General characteristics of the individuals, biochemical parameters checked routinely (white blood cell (WBC), platelet (PLT), lymphocyte, Neutrophil/Lymphocyte (N/L) rate, C-reactive protein (CRP), oxygen (O2) saturation at the time of admission), serum vitamin B12 and folic acid levels, length of stay in intensive care unit (ICU) and hospitalization, and mortality were recorded. Results: The mean age of individuals was 62.8±15.12 years, and 50.9% were men and 49.1% women. The mean level of serum folic acid in the subjects was 9.1±4.91 (ng/mL), and 2.4% had folic acid deficiency and 28.4% had folic acid insufficiency. The mean serum vitamin B12 was 295.6±229.98 (pg/mL), and vitamin B12 deficiency was observed only in 14.4%. The increase in serum folic acid levels reduces the total length of hospitalization and the risk of mortality (p<0.05). On the other hand, no correlation was found between B12 levels and the length of stay in ICU, hospitalization and mortality. It was shown that WBC and N/L rate decreased as serum folic acid levels increased, and O2 saturation at the first hospital admission was higher. Conclusions: Folate deficiency and insufficiency are common among hospitalized COVID-19 patients and cause progression to severe disease. Therefore, examining COVID-19 patients in terms of nutritional deficiencies is critical in monitoring the clinical outcomes of disease